МОDEL OF AIR TRANSPORT LOGISTICS SYSTEM OPERATION IN THE REPUBLIC OF BELARUS AND EVALUATION OF ITS EFFICIENCY - T. R. Kisel; O. L. Polyko (Наука и техника)
The paper specifies a conceptual system of logistics and determines  basic elements of the logistics system of air transport. The methodology for evaluation of logistics system efficiency of international air communication in the Republic of Belarus has been presented in the paper.